Cognitive Decline as a Result of Incarceration and the Effects of a CBT/MT Intervention: A Cluster-Randomized Controlled Trial - Umbach, Rebecca (Criminal justice and behavior, 2018)
This study primarily tests whether incarceration negatively affects cognitive functioning; namely, emotion regulation, cognitive control, and emotion recognition. As a secondary interest, we test protective effects of a cognitive behavioral therapy/mindfulness training (CBT/MT) intervention. Dormitories containing 197 incarcerated males aged 16 to 18 years were randomly assigned to either a CBT/MT program or an active control condition. A cognitive task was administered pretreatment and again 4 months later, upon treatment completion. Performance on all outcome variables was significantly worse at follow-up compared with baseline. There were marginally significant group by time interactions. While the control group performance significantly declined in both cognitive control and emotion regulation, the CBT/MT group showed no significant decline in either outcome. This is the first study to probe the effects of incarceration on these three processes. Findings suggest that incarceration worsens a known risk factor for crime (cognitive functioning), and that a CBT/MT intervention may help buffer against declines.